Light‐driven dynamics between calcification and production in functionally diverse coral reef calcifiers. Issue 2 (8th January 2022) - Mallon, Jennifer; Cyronak, Tyler; Hall, Emily R.; Banaszak, Anastazia T.; Exton, Dan A.; Bass, Adrian M.
Abstract: Coral reef metabolism underpins ecosystem function and is defined by the processes of photosynthesis, respiration, calcification, and calcium carbonate dissolution. However, the relationships between these physiological processes at the organismal level and their interactions with light remain unclear. We examined metabolic rates across a range of photosynthesising calcifiers in the Caribbean: the scleractinian corals Acropora cervicornis, Orbicella faveolata, Porites astreoides, and Siderastrea siderea, and crustose coralline algae (CCA) under varying natural light conditions. Net photosynthesis and calcification showed a parabolic response to light across all species, with differences among massive corals, branching corals, and CCA that reflect their relative functional roles on the reef. At night, all organisms were net respiring, and most were net calcifying, although some incubations demonstrated instances of net calcium carbonate (CaCO3 ) dissolution. Peak metabolic rates at light‐saturation (maximum photosynthesis and calcification) and average dark rates (respiration and dark calcification) were positively correlated across species. Interspecies relationships among photosynthesis, respiration, and calcification indicate that calcification rates are linked to energy production at the organismal level in calcifying reef organisms. The species‐specific ratios of net calcification to photosynthesis varied with light over a diurnal cycle. The dynamic nature of calcification/photosynthesis ratios over a diurnal cycle questions the use of this metric as an indicator for reef function and health at the ecosystem scale unless temporal variability is accounted for, and a new metric is proposed. The complex light‐driven dynamics of metabolic processes in coral reef organisms indicate that a more comprehensive understanding of reef metabolism is needed for predicting the future impacts of global change.